Dampak Imposter Syndrome pada Mahasiswa yang Mengalami Prokrastinasi Akademik dan Peran Pemulihan Psikologis Berbasis Spiritual - Kusuma Nuryani; Dosi Juliawati (UIN Siber Syekh Nurjati Cirebon, 2025)
This research examines the impact of Imposter Syndrome (IS)—internal feelings of unworthiness for achievement despite having external evidence of success—on academic procrastination among outstanding students. Students who experience IS often show a tendency to procrastinate on assignments, which has the potential to hinder their academic potential. The main purpose of this study is to analyze the interrelation between self-doubt, perceived academic pressure, and the role of the psychological recovery process through spiritual approaches (for example, worship practices) in moderating these relationships. This qualitative research uses in-depth interviews and participatory observation for two weeks. The study sample consisted of outstanding students who were identified as experiencing symptoms of IS and procrastination. Data was collected to thoroughly explore emotional dynamics, manifestations of procrastinative behavior, and the role of worship practices in helping students overcome anxiety and pressure. Research results show that feeling inappropriate for success (IS) significantly triggers procrastination, increased anxiety, and emotional fatigue (burnout). Furthermore, the practice of worship was found to have a calming effect, strengthening self-acceptance, and increasing the mental resilience of students. These findings underline the therapeutic and supportive value of the spiritual approach in dealing with academic pressure.